IAd production : beginners guide : create motion-rich, beautiful iAd adverts for iOS devices and incorporate techniques to help boost revenue and brand awareness /: beginners guide : create motion-rich, beautiful iAd adverts for iOS devices and incorporate techniques to help boost revenue and brand awareness. (2012) - Unknown
No abstract available